Pelatihan dan ToT Ekologi Tanah untuk Penguatan Pertanian Organik pada Kelompok Tani Al-Barokah dan Walisongo di Desa Ketapang - Supriyadi Supriyadi; Purwanto Purwanto; Sri Hartati; Galuh Mashitoh; Malihatun Nufus; Widya Aryani (Universitas Sebelas Maret, 2021)
Soil Ecology Training and ToT for Strengthening Organic Agriculture in Al-Barokah and Walisongo Farmer Groups in Ketapang Village. In sustainable integrated agriculture, farmers are expected to be experts in managing agricultural ecosystems. To support this, training and empowerment of sustainable agricultural management can be carried out for farmers. The process of soil ecology training and training of trainers (ToT) is directed at strengthening organic farming and it is hoped that farmers can play a role as a farm manager, able to stand parallel and have an active relationship with the community and have a role in the system built by the community. Therefore, it is proposed the title of PKM-Training and ToT of Ecology Soil for Strengthening Organic Agriculture. The purpose of training and soil ecology ToT for strengthening organic agriculture is to increase farmers' understanding of the importance of ecology in soil management that has been applied so that there is renewal in soil management and building farmer knowledge. Through the Participatory Action Program approach, the Al-Barokah and Walisongo Farmer Groups farmers are very enthusiastic, which is indicated by an increase in understanding of soil ecology. Training and soil ecology ToT for farmers is very important so that soil management is in harmony with nature and increase the understood that soil ecology is part of the global ecosystem, and soil ecology is a process of interaction between ecological components on the level of fertility and crop production.